REGULATION OF TILLERING IN WHEAT AND ITS RELATIONSHIP WITH GRAIN YIELD 1.CONTRIBUTION PERCENTAGES OF THE MAIN STEM AND PRIMARY TILLERING THE NUMBER OF SPIKES AND GRAIN YIELD - & Al- Hassan, Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A Factorial experiment was conducted at the experimental farm of Field Crop College of Agriculture University of Baghdad winter Season of 2014-2015. The study was aimed to investigate the effect of seeding rates and nitrogen levels on regulation of tillering in wheat and its relationship with grain yield and components. Treatments were distributed in the Factorial experiment within Randomized Complete Black Design with three replicates and four seeding rates 60,80,100 and 120 kg ha-1 and fertilized with four nitrogen levels 50,100,150 and 200 kgN.ha-1. The results showed that there were significant differences within two factors and their interaction on the number of spikes and grain yield. Main stem produced the highest number of Spike 210.00 spike.m-2, and grain yield 3.050 tan ha-1 compared to primary tillers (tiller1,tiller2,tiller3). Concerning the seeding rate 80 kg ha-1 resulted in the highest number of Spike.m-2 363 spike and Grain yield 4.775 tan.h-1 compared to other seed rates. The N level 150 kg ha-1 gave the highest number of spikes 382 spike and grain Yield 4.919 tan.h-1 compared to other N levels. The percentage of contribution main stem 50.82, 64.57 % respectively compared to the tillers (tiller1, tiller2, tiller3) which amounted to 32.55, 12.80 and 3.80 % respectively in the spikes number, and 26.02, 7.90 and 1.33 % respectively in grain yield. It could be conclude that the total contribution of the primary tillers percentages represents a half the total number of spikes within two factors of study, while the total contribution percentages of primary tillers is amounted to half the main stem contribution in the grain yield within two factors of study.